American fantasy - Straub, Emma (Riverhead Books, 2026)
"When the 'American Fantasy' cruise ship sets sail for a four-day themed voyage, aboard are all five members of a famous nineties-era boy band and three thousand screaming women who have worshipped them since childhood. Feeling slightly out of place amid this crowd is Annie, newly divorced, fifty years old with an empty nest, and here on a lark to appease her sister. Yet when the lights come up and the idols of her youth begin to sing, something is unlocked. Call it memory. Call it nostalgia. Call it the chemical reaction of hormones, hope, and sexual reawakening. Between the slushy alcoholic drinks, the familiar music, and the throngs of middle-aged women acting like lovesick teenagers, Annie finally reconnects to a long-submerged part of herself. By the time she meets one of the band members--not just a celebrity but someone in need of a friend--she has accessed a new sense of possibility"--Inside jacket flap.